A Search for the Oblique Effect in Young Infants - Martello, Lorraine Myrna (My University, 1978)
For a wide variety of visual tasks, subjects perform more poorly when stimuli are oriented obliquely than when they are oriented vertically or horizontally. It is generally believed that this 'oblique effect' has two manifestations. One is meridional anisotrophy, i.e., lower acuity for obliquely oriented stimuli than for vertical or horizontal stimuli. The second is poor oblique discrimination; i.e., greater difficulty discriminating between mirror-image oblique stimuli than between vertical and horizontal ones, even when the stimuli are above the threshold of acuity. This thesis explores whether these two phenomena are in fact both manifestations of the same effect.
Chapter One provides a detailed survey of studies showing meridional anisotrophy and considers the nature of its etiology and development. Chapter Two provides a review of the existing literature on the discrimination problem as evidenced in young children. The author argues that while meridional anisotrophy and poor oblique discrimination by young children appear to be related phenomena, it is possible that both are not manifestations of the same effect. The author tested this possibility by comparing the developmental course of poor oblique discrimination with the know developmental course of meridional anisotrophy.
Chapters Three through Six present four experiments in which the author tested young infants' ability to discriminate between mirror-image oblique stripes with their ability to discriminate between "vertical-and horizontal ones, with the stripes above the threshold of acuity. In one experiment six week olds were tested; in the other three, 17-18 week old infants were tested using different variants of the habituation procedure.
The major finding of the research is that neither 6 week nor 17-18 week old infants, both of whom are known to show meridional ranisotrophy, show evidence that a mirror-image oblique discrimination is more difficult than a discrimination between a vertical and horizontal. Furthermore, modification of the testing procedure, so that it more closely mimics a task in which children show difficulty discriminating mirror-image oblique lines, does not appear to affect 17-18 week olds discrimination performance.
In the final chapter, the author discusses the implications of the research findings. The author concludes that since infants known to show meridional anisotrophy do not show poor oblique discrimination, then it is probable that these two phenomena are not both manifestations of the same effect nor do they appear to be generated by the same underlying mechanism. The author also discusses the implications of the research findings for two cognitive theories which have been advanced to explain how children process obliquely oriented stimuli.
Keywords: Medical Sciences; Medical Sciences